Joint energy and reserve market design with explicit consideration on frequency quality - Jin Ma (Wiley, 2021)
Abstract Energy and reserve markets are two important market components in the deregulated power industry. Energy markets provide a platform for generating companies, retailers, and big energy consumers to centrally trade electricity. However, owing to the varying renewable power generation, load variation and unexpected contingencies, energy supply and consumption always embody high uncertainties. Furthermore, due to the lack of low‐cost, large‐capacity energy storage devices, an instant balance between the generation and load is required under these uncertainties. Therefore, the reserve market is set up to address the balance‐disruptive uncertainties intrinsic to the power grid. Although this combined market design reduces the risk of the possible imbalance in energy supply and consumption, it does not guarantee that the frequency of the grid is satisfactory, even in the normal operation. This study analyzes the insufficiency of the energy and reserve market design in addressing frequency quality problems by exploring the root causes for the deteriorating frequency quality in the Australian National Electricity Market. A novel framework that incorporates the frequency quality, control capacity, and control cost to achieve the desired frequency quality is then presented. Case studies through a simple power system and the IEEE 30‐bus system demonstrate the efficacy of the presented methods.